Gaya Hidup Hedonisme dan Perilaku Konsumtif Remaja Putri Kota Kupang - Hamzah Nazarudin; Tantri Widiastuti (Jurnal Ilmiah Aset, 2022)
The purpose of this study was to find out the influence of hedonism lifestyle on the consumptive behavior of young women in Kupang City. The subjects of this study were female consumers aged 18 to 21 years who visited the SPC handphone store in Kupang city. The date were collection thorough questionnaires. Sampling techniques using axidental sampling. Sampling techniques according to hair et al. (2010). The determination of the number of samples represented depends on the number of indicators multiplied by 5 to 10. the writer collects data by spreading questionnaires to 50 respondents of young women who shopped at the SPC handphone store koanino Kupang city. Technique for analyzing data was simple linear regression analysis. The results showed that there was a positive influence between hedonism lifestyles on the consumptive behavior of young women in the Kupang city. The higher the lifestyle of hedonism, the higher the consumptive behavior of young women of Kupang City and the lower the lifestyle of hedonism, the lower the consumptive behavior of the young women of kupang city.